2015
DOI: 10.18034/abcjar.v4i2.51
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Customers’ Satisfaction Regarding Different Services of Mobile Telecom Operator Companies in Bangladesh: An Evaluation

Abstract: The purpose of the present research study is to measure the customer satisfaction regarding the different services of the mobile telecom operator companies in Bangladesh. The mobile telecom sectors are growing rapidly and the contribution of this sector to economic development is very significant. The study surveyed 150 users' opinions to determine the satisfaction level regarding the different services of the mobile telecom operator companies in Bangladesh. On the basis of findings it is evident that the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similar to our research, Kumar et al (2016) found that CRM technology and knowledge management, customer orientation, and CRM organization significantly positively impact organizational performance. Sarker et al (2015) said that CRM, perceived and throughout its improvement organization, can catch and hold economically valued customers and aside less money-making customers, which places CRM in line with contemporary customer-centric business management theory. Valuing customers will lead any business to achieve long-term partnerships and thus increase the organization's performance.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar to our research, Kumar et al (2016) found that CRM technology and knowledge management, customer orientation, and CRM organization significantly positively impact organizational performance. Sarker et al (2015) said that CRM, perceived and throughout its improvement organization, can catch and hold economically valued customers and aside less money-making customers, which places CRM in line with contemporary customer-centric business management theory. Valuing customers will lead any business to achieve long-term partnerships and thus increase the organization's performance.…”
Section: Discussionmentioning
confidence: 87%
“…In a simple word, Customer relationship management can be defined as the process of generating relationships with customers, retaining the relationship smoothly, and enlarging the relationship effectively. Sarker et al (2015) state, "Customer Relationship Management is a comprehensive approach for creating, maintaining and expanding customer relationships". According to Thompson (2001crmguru.com), Customer Relationship Management (CRM) is a business strategy to select and manage valuable customer relationships.…”
Section: Conceptual Framework Of Crmmentioning
confidence: 99%